2014
DOI: 10.1111/psyp.12288
|View full text |Cite
|
Sign up to set email alerts
|

Taking the pulse of aging: Mapping pulse pressure and elasticity in cerebral arteries with optical methods

Abstract: Cerebrovascular support is crucial for healthy cognitive and brain aging. Arterial stiffening is a cause of reduced brain blood flow, a predictor of cognitive decline, and a risk factor for cerebrovascular accidents and Alzheimer's disease. Arterial health is influenced by lifestyle factors, such as cardiorespiratory fitness (CRF). We investigated new noninvasive optical measures of cerebrovascular health, which provide estimates of arterial pulse parameters (pulse pressure, transit time, and compliance/elasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
144
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(162 citation statements)
references
References 140 publications
12
144
6
Order By: Relevance
“…Besides a reduction of cerebral blood flow, the ageing brain shows a decreased glucose and oxygen metabolism [15-17]. Similarly, it has been revealed that the retinal blood flow and metabolic demand decrease incrementally with age [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Besides a reduction of cerebral blood flow, the ageing brain shows a decreased glucose and oxygen metabolism [15-17]. Similarly, it has been revealed that the retinal blood flow and metabolic demand decrease incrementally with age [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…We applied this approach to study the correlates of arterial health in a large sample of normally aging healthy adults (age range ¼ 55 to 87), none of whom had any history of stroke or other major health problems. 64 In this sample, as predicted, pulse amplitude was positively correlated with age; the pulse relaxation function was instead positively correlated with measures of cardiorespiratory fitness (CRF) (see Fig. 4), but also with measures of cortical volume, white matter volume, and total cortical volume, indicating that more elastic arteries are associated with more preserved brain tissue in aging.…”
Section: Optical Pulse Signal: From Blood Vessels To Brainmentioning
confidence: 96%
“…65). However, we 64 have recently shown that the optical pulsation signal, or pulse-DOT (if measured using a sampling rate exceeding 20 Hz), in fact provides very useful data about the state of cerebral arteries. First, consistent with its arterial origin, the signal is oxygen-saturated >95%.…”
Section: Optical Pulse Signal: From Blood Vessels To Brainmentioning
confidence: 99%
“…To overcome these limitations, we recently developed a new procedure to assess local cerebrovascular health using near-infrared (NIR) light (Fabiani et al, 2014; Tan et al, 2016; see also Tan et al, 2017). This technique involves injecting NIR light through the scalp and detecting the backscattered light at a certain distance from the light source.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, pulsation data can be easily obtained using the same procedures employed for functional near infrared spectroscopy (fNIRS; Hoshi & Tamura, 1993; Murkin & Arango, 2009; Villringer & Chance, 1997). The optical arterial pulse obtained in this fashion is a very large signal, easily identifiable in each individual subject and at each recording location without averaging, although even greater reliability can be achieved by averaging over a few minutes of recording (Fabiani et al, 2014; Tan et al, 2017). …”
Section: Introductionmentioning
confidence: 99%